2021
DOI: 10.1093/ehjacc/zuab078
|View full text |Cite
|
Sign up to set email alerts
|

Helmet continuous positive airway pressure vs. high flow nasal cannula oxygen in acute cardiogenic pulmonary oedema: a randomized controlled trial

Abstract: Aims  Non-invasive ventilation represents an established treatment for acute cardiogenic pulmonary oedema (ACPO) although no data regarding the best ventilatory strategy are available. We aimed to compare the effectiveness of helmet CPAP (hCPAP) and high flow nasal cannula (HFNC) in the early treatment of ACPO. Methods and results  Single-centre randomized controlled trial of patients admitted to the emergency department due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…One prospective study in hypercapnic patients with cardiogenic pulmonary edema found no difference in CO 2 clearance or work of breathing, 17 whereas a retrospective study showed increased odds of failure with patients with cardiogenic pulmonary edema or hypercapnia when treated with NHF. 18 The only published trial comparing the NHF with NIPPV showed helmet CPAP had a greater improvement in respiratory failure at 1 h. 19 Little is known about the physiologic effects of NHF on acute cardiogenic pulmonary edema. However, given that NHF increases end-expiratory lung volume without the required positive intrathoracic pressure, the benefit for ADHF patients is likely from improved lung mechanics and gas exchange rather than myocardial performance.…”
Section: Controversy #1: Should Patients With Adhf Be Treated With Ni...mentioning
confidence: 99%
“…One prospective study in hypercapnic patients with cardiogenic pulmonary edema found no difference in CO 2 clearance or work of breathing, 17 whereas a retrospective study showed increased odds of failure with patients with cardiogenic pulmonary edema or hypercapnia when treated with NHF. 18 The only published trial comparing the NHF with NIPPV showed helmet CPAP had a greater improvement in respiratory failure at 1 h. 19 Little is known about the physiologic effects of NHF on acute cardiogenic pulmonary edema. However, given that NHF increases end-expiratory lung volume without the required positive intrathoracic pressure, the benefit for ADHF patients is likely from improved lung mechanics and gas exchange rather than myocardial performance.…”
Section: Controversy #1: Should Patients With Adhf Be Treated With Ni...mentioning
confidence: 99%
“…Osman et al conducted a randomized controlled trial comparing HFNOT to non-invasive ventilation (helmet CPAP) in adult patients presenting the emergency room with acute cardiogenic pulmonary oedema ( 90 ). They found CPAP to be more effective in the very short term in improving dyspnoea, hemodynamics and respiratory parameters.…”
Section: High-flow Nasal Oxygen Therapy In Human Medicinementioning
confidence: 99%
“…Only recently the use of HFNO has been investigated in patients with cardiogenic pulmonary edema and, to date, a limited number of studies is available. Two randomized trials found that, compared to oxygen therapy, HFNO reduced respiratory rate without any significant effect on the need for intubation or mortality [ 107 , 123 ]. However, when HFNO was compared to helmet CPAP, although both systems improved the respiratory rate and PaO 2 /FiO 2 , greater improvements were observed in the helmet CPAP group, possibly related to the lower level of positive end-expiratory pressure (PEEP) actually applied by HFNO relative to CPAP [ 107 , 124 ].…”
Section: Management Of Acute Dyspnea With Non-invasive Respiratory Su...mentioning
confidence: 99%